Foreign Employment and its Impact on Human Resource Management for Supply Chains - Leqaa Shaker Abood; Salam Abdul Rahman A. Shalan Al Ibrahim (International Journal of Supply Chain Management, 2019)
Abstract - The aim of the research is to determine the impact of foreign employment on Human Resource Management for Supply Chains of labor market in Iraq, the areas in which it operates, the reasons for its recruitment, the ways in which national employment can replace foreign employment and the reduction of unemployment in the size of the labor force. The research aims at finding out the impact of foreign labor on the labor market in Iraq, the fields in which these workers work, the reasons that led to their importation, and the ways that lead to the possibility of replacing the foreign workers with the national labor force. The research found that most foreign workers are of unskilled labor with less pay and longer working hours, and this justifies their recruitment, which means that local workers with skilled skills are more affected by the increasing numbers of foreign workers. Therefore, it is necessary to protect national workers against foreign labor competition. In the labor market through the establishment of strict laws protect the local factor and restrict the work of foreign workers and contribute to the stability of wage rates